Une cli-fi composite : les artefacts science-fictionnels dans Hors sol de Pierre Alferi - Julia Ori (ReS Futurae)
Pierre Alferi (1963), a poet and novelist who is known for the innovative nature of his texts, presents in Hors sol (2018) a post-apocalyptic world where only a tiny part of humanity has survived, in gondolas suspended in the stratosphere, while the rest has disappeared as a result of the many catastrophes caused by climate change. In contrast to traditional cli-fi, which is linked to popular genres such as thriller, this novel is strongly characterised by its concern for form: it presents a compilation of very heterogeneous texts, which are available online at a specific date in the early 22nd century. This amalgam of documents gives a fairly complete picture, not only of this post-apocalyptic world, but also of the causes of the exile in the sky. In this article, the study of dialogism (Bakhtin)—particularly the subversion of official discourses—and the polyphonic nature of the novel—its fragmentation and the way in which different texts are presented—will be proposed in order to demonstrate that Pierre Alferi uses juxtaposed fragments to create a nuanced image of the fictional universe, combining elements of science fiction with a commitment to addressing climate change.